(untitled) (Vietnam Journal of Community Medicine, 2024)
Introduction: Perilunate dislocations are rare high- enery injuries constituting less than 10% of all wrist injuries. The carpus consists of two rows of bones: proximal and distal. The proximal row, which is the more mobile of the two, articulates with the distal radius and moves in concert with the distal radius and ulna. The scaphoid, lunate, and triquetrum serve as the connecting bones that make up the proximal row. The more rigid distal row- which contains the trapezium, trapezoid, capitate, and hamate serves as a bridge between the proximal row and metacarpal bases. Perilunate injuries should, therefore, be focused and ruled out while examining a patient complaining wrist pain after high-energy accidents which are often missed. Three Cases report: We reported 3 cases of, missed the diagnosis of perilunate dislocation, with signs of post-traumatic wrist pain and limited wrist movement. Patients were diagnosed and treated with open reduction surgery, internal fixation when there was a fracture, repair or reconstruction of the scapholunate ligament. Aggressive wrist physiotherapy retrieved near-normal range of motion at the wrist by the end of 24 months as well as neither revealed recurrence of the dislocation nor signs of avascular necrosis. Conclusion: Succesful results in the treatment of perilunate dislocations can be obtained with open reduction, internal fixation when there was a fracture, repair or reconstruction of the scapholunate ligament. The result is almost normal wrist range of motion recovery.